Organic-Ruthenium(II) Polypyridyl Complex Based Sensitizer for Dye-Sensitized Solar Cell Applications. (24th July 2011) - Giribabu, Lingamallu; Singh, Varun Kumar; Vijay Kumar, Challuri; Soujanya, Yarasi; Gopal Reddy, Veerannagari; Yella Reddy, Paidi
Abstract : A new high molar extinction coefficient organic-ruthenium(II) polypyridyl complex sensitizer (RD-Cou ) that contains 2, 2 ′, 6, 6 ′ -tetramethyl-9-thiophene-2-yl-2, 3, 5, 6, 6a, 11c-hexahydro1H, 4H-11oxa-3a-aza-benzoanthracene-10-one as extendedπ -conjugation of ancillary bipyridine ligand, 4, 4 ′ -dicaboxy-2, 2 ′ 6 ′, 2 ′′ -bipyridine, and a thiocyanate ligand in its molecular structure has been synthesized and completely characterized by CHN, Mass, 1 H-NMR, UV-Vis, and fluorescence spectroscopies as well as cyclic voltammetry. The new sensitizer was tested in dye-sensitized solar cells using a durable redox electrolyte and compared its performance to that of standard sensitizerZ-907 .